Analysis of Incident Light Angles on Nanograting Structure for Minimizing Reflection Losses in GaAs Solar Cells - Das, Narottam; Charoenpitaks, Korawat; Islam, Syed (University of Tasmania, 2013)
Subwavelength grating (SWG) structures make an excellent alternative antireflective (AR) coating due to its capacity to reduce the reflection losses in GaAs solar cells. The SWG structures allow the gradual change in refractive index that confirms an excellent AR coating and the light trapping properties when compare with planar thin film structures. Finite-difference time domain (FDTD) method is used to simulate the reflection losses of the SWG structure in GaAs solar cells. The FDTD simulation results show that the slightly change of incident angle affect the reflection losses of all nano-grating structure. The simulation results also confirmed that the reflection loss of nano-grating structure maintained optimum within ~±5° of incident angle tolerance for the grating height over 300-nm for minimizing the reflection losses in GaAs solar cells.